2016
DOI: 10.1038/srep36545
|View full text |Cite
|
Sign up to set email alerts
|

DHA-supplemented diet increases the survival of rats following asphyxia-induced cardiac arrest and cardiopulmonary bypass resuscitation

Abstract: Accumulating evidence illustrates the beneficial effects of dietary docosahexaenoic acid (DHA) on cardiovascular diseases. However, its effects on cardiac arrest (CA) remain controversial in epidemiological studies and have not been reported in controlled animal studies. Here, we examined whether dietary DHA can improve survival, the most important endpoint in CA. Male Sprague-Dawley rats were randomized into two groups and received either a control diet or a DHA-supplemented diet for 7–8 weeks. Rats were then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 49 publications
(63 reference statements)
0
12
0
Order By: Relevance
“…The rats were intubated, mechanically ventilated, and instrumented under anesthesia with 2% isoflurane as described previously [ 15 19 ]. End-tidal carbon dioxide (EtCO 2 ) was maintained at 40 ± 5 mmHg during the experiment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rats were intubated, mechanically ventilated, and instrumented under anesthesia with 2% isoflurane as described previously [ 15 19 ]. End-tidal carbon dioxide (EtCO 2 ) was maintained at 40 ± 5 mmHg during the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…This study used a rat model of highly lethal prolonged asphyxia‐induced CA, as reported previously [ 15 19 ]. In our previous studies, the survival rate was ~ 20% at 4 h after CA/ECPR [ 19 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Lipids are fundamentally important for energy storage, cell membrane structure and cellular functions (Sunshine & Iruela‐Arispe, 2017). Studies suggest that within lipids, the omega‐3 (n–3) polyunsaturated fatty acids (PUFA), in particular alpha‐linolenic acid (ALA; 18:3n‐3), eicosapentaenoic acid (EPA; 20:5n‐3), and docosahexaenoic acid (DHA; 22:6n‐3), can be important for somatic development, especially for nervous and gonadal tissues (Arts & Kohler, 2009; Guo et al, 2016a; Tocher et al, 2019), cognition (Cunanne et al, 2009; Hoffman et al, 2009; McCann & Ames, 2005), reproduction (Chen et al, 2012; Martin‐Creuzburg et al, 2009; Roqueta‐Rivera et al, 2010; Sinendo et al, 2017) and survival (Fuiman & Perez, 2015; Kim et al, 2016; Matsunari et al, 2013; Mesa‐Rodriguez et al, 2018; Twining et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Adaptation, behavior, diversification, genetics, metabolic networks, nutritional landscapes, omega-3 polyunsaturated fatty acids, traits 2009; Hoffman et al, 2009;McCann & Ames, 2005), reproduction (Chen et al, 2012;Roqueta-Rivera et al, 2010;Sinendo et al, 2017) and survival (Fuiman & Perez, 2015;Kim et al, 2016;Matsunari et al, 2013;Mesa-Rodriguez et al, 2018;.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental protocol was approved by the Institutional Animal Care and Use Committee of the University of Pennsylvania (#804889). The detailed surgical procedures were provided in supplementary materials [13]. Male adult Sprague-Dawley rats were used.…”
Section: Asphyxial Ca and Cpb Resuscitationmentioning
confidence: 99%